2016
DOI: 10.4172/2157-7110.1000546
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Incorporating Whey Protein Concentrate on Chemical, Rheological and Textural Properties of Ice Cream

Abstract: Effect of whey protein concentrate as a partial substitution of milk solids not fat in ice cream formula was investigated by replacing 1, 2, 3 and 4% of mix solid not fat. Mixes and resultant ice cream samples were evaluated for their chemical, physicochemical, and rheological properties as well as the sensory quality attributes. Implementing whey protein concentrate in ice cream recipes increased total protein, freezing point and consistency, while, ash, lactose, specific gravity decreased significantly (p<0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
(29 reference statements)
1
0
0
1
Order By: Relevance
“…In parallel with our results, El‐Zeini et al. ( 2016 ) reported that ice creams with a higher overrun ratio exhibit lower hardness values when fresh or after 14 days of storage. Also, the increase in hardness depending on the storage period could be due to recrystallization of the ice (BahramParvar et al., 2013 ).…”
Section: Resultssupporting
confidence: 92%
“…In parallel with our results, El‐Zeini et al. ( 2016 ) reported that ice creams with a higher overrun ratio exhibit lower hardness values when fresh or after 14 days of storage. Also, the increase in hardness depending on the storage period could be due to recrystallization of the ice (BahramParvar et al., 2013 ).…”
Section: Resultssupporting
confidence: 92%
“…Sensory tests of the cream samples were conducted by several panelists experienced in the field of dairy from the Department of Food Science / College of Agriculture and Forestry / University of Mosul, and the scores were awarded according to the sensory evaluation of Flavor (45), Body and texture (30), Color and appearance (15), Spreadability (10)] forms created by Clark and Costello (2009).…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…При использовании концентратов сывороточных белков в количестве до 3 % повышается биологическая ценность белков сливочного мороженого на 15 % [8]. Многие исследователи экспериментально обосновали положительное влияние концентратов белков на физические [9], химические, реологические, органолептические и текстурные показатели качества мороженого [10][11][12]. Установлено положительное влияние концентратов сывороточных белков при высокой массовой доле на физические и сенсорные свойства мороженого с пониженной массовой долей жира [13] и при использовании трансглутаминазы [14].…”
Section: Introductionunclassified